The relationship between serum 25-hydroxyvitamin D levels and the severity of COVID-19 disease and its mortality - Maryam Vasheghani (Nature Portfolio, 2021)
Abstract Supplemental vitamin D can reduce the risk and mortality of viral pneumonia. The relationship between 25 hydroxyvitamin D [25(OH)D] levels and the severity and mortality of Coronavirus disease 2019 (COVID-19) was evaluated. In this cross-sectional study, the admitted patients with COVID-19 were categorized as mild, moderate, severe, and critical based on clinical and radiologic characteristics. Calcium, phosphorus, albumin, creatinine, and serum 25(OH)D were measured and their correlation with the severity of disease and mortality were analyzed. During 2 months, 508 patients (442 patients in general wards and 66 patients in the intensive care unit (ICU)) were included. The participants were 56 ± 17 years old (52% male, 37% with comorbidity). Concerning severity, 13%, 42%, 36%, and 9% had mild, moderate, severe, and critical diseases, respectively. The mortality rate was 10.8%. Admission to ICU, severity of disease and mortality decreased significantly across quartiles of 25(OH)D. According to multivariate logistic regression analysis, disease mortality had a positive correlation with age and had a negative correlation with the serum level of 25(OH)D, calcium, and albumin. In hospitalized patients with COVID-19, low 25(OH)D was associated with severe disease and increased ICU admission and mortality rate.